PENGARUH KEPEMIMPINAN, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN TANAMAN PANGAN PROVINSI JAWA BARAT - Suryadana, M. Liga; Hardiyana, Aan; Yahya, Asep (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2014)
The purpose of this study was to determine the effect of leadership, competence and Compensation Employee Performance Against the Department of Agriculture of West Java Province ". The research was done by taking the entire population of Employees in Department of Agriculture of West Java Province. The method used is descriptive method of analysis, the number of respondents 80 employees (population). Analysis of the results of this study using path analysis. The results of the research are: Overview of leadership, reaching an average score of 4.53. The average score in accordance with the table interpretation criteria including the excellent category. Competence picture that achieved an average score of 4.50. The average score is consistent with the interpretation criteria including the excellent category. Overview Compensation which achieved an average score of 4.13 The average score is consistent with the interpretation criteria including the excellent category. Picture of employee performance, reaching an average of 4.59. The average score is consistent with the interpretation criteria including the excellent category. The influence of leadership on employee performance, ie the direct effect of 15.20%. Indirect effect through the Competence of 10.60%, and through compensation of 3.30%. Thus the effect totaled 29.10% .. Influence of Competence on employee performance, ie the direct effect of 23.00%. Indirect effect through the leadership of 10.60%, and through compensation of 6.00%. Thus the effect of a total of 39.60%. Compensation Effect on employee performance, ie the direct effect of 7,20%. Indirect influence through leadership by 3.30% and amounted to 6.00% through competence. Thus the effect of a total of 16.50%. The influence of leadership, competence, and compensation to employee performance employee at Department of Agriculture of West Java Province, simultaneously at 85.20%. It shows that there is a significant effect. Keywords: leadership; competence; compensation; employee performance